The Metamorphosis of Marketing Communication Media: Strategy to Cultivate Digital Marketing Enthusiasm and Creativity in Batik Business Products - Suharyanto, Deny Feri; Rasaili, Wilda; Andiriyanto, Ach.; ,, Zarnuji; Arista Rahman, Sindi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2023)
The determination of technology has changed the face of the world in all sectors, the industrial and trade sectors in particular have a very significant impact. The technological revolution that touches all joints really forces all business people, in this case entrepreneurs, to move from conventional manual to digital. Even so, this internet technology revolution cannot suddenly get out of hand. It is necessary to test the readiness of the community to implement this digital technology. The research method uses descriptive qualitative through data collection by means of interviews, observation and FGD. The findings obtained are that the application of digital marketing is not optimal because it only relies on social networks. The implementation of digital marketing is carried out through stages, training and development followed by the implementation of programs that are adapted to the conditions at the Fahira Batik Collection. The results of the research are in the form of web-based e-commerce information technology development training and optimization of social media for craftsmen, training to improve the brand of Fahira Batik Collection products. So with this it is hoped that the craftsmen can expand their marketing reach by promoting their products through various social media so that it is expected to increase the income and welfare of the craftsmen. Keywords: Digital Marketing, Commercialization, Technology, Communication